Urban literacies: guidelines to qualify popular participation in land regularization projects (PerCursos, 2024)
The research that underpins this article is focused on the recognition of rights, aiming at the effective participation of the population in Urban Land Regularization (REURB) processes. In this context, the article aims to define principles to qualify popular participation in REURB projects, starting from the debate on Popular Education as the main avenue for the political formation of citizens. The research contributes to the field of studies on formative processes based on the pedagogical proposal of Popular Education within the scope of REURB projects. It is a bibliographical investigation of qualitative approach, carried out through the technique of content analysis, with the aid of the MAXQDA software. The analyzed data come from 26 booklets produced by federal, state, and municipal agencies, covering the period between the approval of the Statute of Cities in 2001 and three years after the promulgation of the last legislation dealing with land regularization in 2020. The results highlight the absence of a dialectical relationship between the producers of the booklets and the target audience, emphasizing the need to improve the debate on Brazilian housing policy, emphasizing the relevance of formative processes based on the pedagogical proposal of Popular Education.
Keywords: popular education; popular participation; land regularization - REURB